Using Rasch Analysis to Validate the Michigan Hand Outcomes Questionnaire from the Wrist and Radius Injury Surgical Trial. Issue 4 (October 2021) - Jayaram, Mayank; Wang, B.S., Chang; Shauver, Melissa J.; Wang, Lu; Chung, Kevin C.
Abstract : Background: The Michigan Hand Outcomes Questionnaire is a patient-reported outcome measure that has been validated in many upper extremity disorders using classic test theory. Rasch measurement analysis is a rigorous method of questionnaire validation that offers several advantages over classic test theory and was used to assess the psychometric properties of the Michigan Hand Outcomes Questionnaire. This study used Rasch analysis to evaluate the questionnaire for distal radius fractures in older adults. The incidence and costs of distal radius fractures are rising, and reliable assessment tools are needed to measure outcomes in this growing concern. Methods: Rasch analysis was performed using 6-month assessment data from the Wrist and Radius Injury Surgical Trial. Each domain in the Michigan Hand Outcomes Questionnaire was independently analyzed for threshold ordering, person-item targeting, item fit, differential-item functioning, response dependency, unidimensionality, and internal consistency. Results: After collapsing disordered thresholds and removing any misfitting items from the model, five domains (Function, Activities of Daily Living, Work, Pain, and Satisfaction) demonstrated excellent fit to the Rasch model. The Aesthetics domain demonstrated high reliability and internal consistency but had poor fit to the Rasch model. Conclusions: Rasch analysis further supports the reliability and validity of using the Michigan Hand Outcomes Questionnaire to assess hand outcomes in older adults following treatment for distal radius fractures. Results from this study suggest that questionnaire scores should be interpreted in a condition-specific manner, with more emphasis placed on interpreting individual domain scores, rather than the summary Michigan Hand Outcomes Questionnaire score.